A Deep Overview of Anticoagulant Drugs: Recent Synthesis and Their Activity Assay - Engrid Juni Astuti; Slamet Ibrahim; Muhammad Ali Zulfikar; Sophi Damayanti (Indonesian Journal of Chemistry, 2024)
During the unprecedented COVID-19 pandemic, anticoagulant drugs have emerged as a crucial component of treatment alongside antivirus medications. Patients with severe COVID-19 frequently have critical conditions marked by blood clot development, necessitating the administration of anticoagulants. This review aims to provide a comprehensive overview of various anticoagulant drugs, their synthesis methods, and assays employed to predict their anticoagulant activity. Notable anticoagulant categories frequently utilized include oral anticoagulants heparin, non-vitamin K antagonists, and vitamin K antagonists. In recent years, the development of new anticoagulants has seen a shift towards a multifaceted approach that combines in silico prediction with in vitro and in vivo assays. In silico prediction techniques play a pivotal role in the initial screening process. This integrated approach has yielded promising results, paving the way for the synthesis of novel anticoagulant candidates, as substantiated by a battery of in vitro, in vivo, and ex-vivo tests.